Evaluation of motion on underwater monofin swimming for novice - Tanigawa, T.; Terada, M.; Kataoka, H.; Matsumoto, T.; Kamiya, M.; Taguchi, A.; Kida, N.; Nomura, T. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
This study aims to evaluate the relationships between horizontal velocity, kick rate, kick length, and the range of motion of each body part in apnea finswimming. Research was conducted on 81 male and 26 female high-school swimmers without monofin swimming experience. Each subject swam at their maximum performance during the test. Measurements for motion analysis were taken for the wrists, elbows, shoulders, hips, knees, ankles and the tip of the monofin. We used the vertical displacement of each body part over time to approximate a sine wave (z=a1 *sin (b1 *t+c1) +d1 *t+e1). Using these figures, we observed the following three points. 1) For male subjects, no correlations were observed between horizontal velocity and the length of amplitudes of the wrists, elbows, shoulders, hips and knees. For females, no correlations were found between horizontal velocity and the length of amplitudes of the shoulders and hips.2) There was a negative correlation between kick rate and amplitudes for both males and females (Elbow r = -.660, p<.Ol) 3) There was a significant positive correlation between kick length and the amplitudes of the lower limbs. (Males: Ankle r=.888 p<.Ol, Females: Ankle r=.863 p<.01)